The Effectiveness of Cognitive-Behavioral Therapy on Death Anxiety and Trauma Avoidance in Women with Breast Cancer - Maghhoori, Mona; Ghanadzadegan, Hosseinali; Chamani, Alireza (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to determine the effectiveness of cognitive-behavioral therapy in reducing death anxiety and trauma avoidance among women with breast cancer.Methods and Materials: The research employed a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of all women with breast cancer referred to a comprehensive cancer center in 2025, from which 20 participants were selected through purposive sampling and randomly assigned to experimental and control groups (10 participants in each group). Data were collected using the Collett–Lester Death Anxiety Scale and the Trauma Avoidance Questionnaire. The experimental group received an eight-session cognitive-behavioral therapy intervention, while the control group received no psychological treatment. The intervention included cognitive restructuring, relaxation training, emotional awareness, and behavioral techniques aimed at reducing maladaptive coping patterns. Data were analyzed using multivariate analysis of covariance (MANCOVA) to examine the effect of the intervention while controlling for pretest scores.Findings: The results of multivariate analysis of covariance indicated a significant overall effect of cognitive-behavioral therapy on the combined dependent variables (p ≤ 0.01). Univariate analyses revealed that, after controlling for pretest scores, there were significant differences between the experimental and control groups in both death anxiety (F = 14.971, p = 0.001, η² = 0.416) and trauma avoidance (F = 6.914, p = 0.016, η² = 0.257), indicating that the intervention significantly reduced these variables in the experimental group.Conclusion: The findings suggest that cognitive-behavioral therapy is an effective intervention for reducing death anxiety and trauma avoidance in women with breast cancer.